Georges Florovsky and the Russian religious renaissance - Gavrilyuk, Paul L. (Changing paradigms in historical and systematic theology, 2014)
This study offers a new interpretation of 20th-century Russian Orthodox theology by engaging the work of Georges Florovsky (1893-1979), especially his programme of a 'return to the Church Fathers', analysing how Florovsky's evolving interpretation of Russian religious thought, particularly Vladimir Solovyov and Sergius Bulgakov, informed his approach to patristic sources.